Kepemimpinan Inklusif sebagai Determinan Perilaku Proaktif: Peran Mediasi Rasa Syukur di Tempat Kerja - Armansyah Novendra; Adolf Bastian; Ririn Handayani (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The study was conducted at the Pelalawan Regency Land Office, with the aim of testing the role of gratitude in the workplace in mediating the influence of inclusive leadership on proactive behavior. The population of this study was 98 people. Based on this population size, the entire population was sampled. The sampling method used in this study was the Saturated Sampling Technique. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that Inclusive leadership has a positive effect on proactive behavior; Inclusive leadership has a positive effect on gratitude in the workplace; Gratitude in the workplace has an effect on proactive behavior; Gratitude mediates the effect of inclusive leadership on proactive behavior.